1999
DOI: 10.1007/s004490050697
|View full text |Cite
|
Sign up to set email alerts
|

A new training method for hybrid models of bioprocesses

Abstract: Modeling of bioprocesses for engineering applications is a very dif®cult and time consuming task, due to their complex nonlinear dynamic behavior. In the last years several propositions for hybrid models, and especially serial approaches, were published and discussed, in order to combine analytical prior knowledge with the learning capabilities of Arti®cial Neural Networks (ANN). These approaches often require synchronous and equidistant sampled training data. However, in practice concentrations are mostly off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…By using this hybrid model in a fed-batch process, they were able to increase the final productivity of IgG1-IL2 by 10 % (Teixeira et al 2007 ). Graefe et al ( 1999 ) applied a serial hybrid model to CHO-K1 by combining mass balances and neural network kinetics. A convincing prediction of components concentrations in the stirred tank bioreactor was achieved.…”
Section: Macroscopic Kinetic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using this hybrid model in a fed-batch process, they were able to increase the final productivity of IgG1-IL2 by 10 % (Teixeira et al 2007 ). Graefe et al ( 1999 ) applied a serial hybrid model to CHO-K1 by combining mass balances and neural network kinetics. A convincing prediction of components concentrations in the stirred tank bioreactor was achieved.…”
Section: Macroscopic Kinetic Modelsmentioning
confidence: 99%
“…LMA was also used by Vande Wouwer et al ( 2004 ) for batch CHO cell culture. LMA was applied in the training process for hybrid models of bioprocesses (Graefe et al 1999 ). Dorka et al ( 2009 ) successfully identified Monod-type parameters of hybridoma cell culture during exponential phase by using quadratic programming (QP).…”
Section: Model Calibration and Testingmentioning
confidence: 99%
“…Additionally, computer simulations based on a process model are useful to reduce the number of experiments with the real biological processes, which are expensive, and particularly time consuming [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rare and asynchronous measurements of biomass, glutamine, glucose and lactate concentrations were performed in batch CHO (Chinese Hamster Ovaries) cell cultures (for details about the experimental conditions, see (Graefe et al, 1999)). In order to describe the macroscopic phenomena occurring in these cultures, a simple reaction scheme is proposed:…”
Section: Real-case Applicationmentioning
confidence: 99%